2014
DOI: 10.1177/1088767914538637
|View full text |Cite
|
Sign up to set email alerts
|

The Profiles of Victims, Perpetrators, and Unfounded Beliefs in Honor Killings in Turkey

Abstract: Despite Turkey's increasing awareness of honor killings, many unfounded beliefs and assumptions still pervade concerning the general profiles of victims, perpetrators, and the crimes committed. These erroneous views are predicated upon a plethora of weak generalizations rather than robust research evidence. Yet, such claims have a significant impact on both the regulations aiming to combat these killings and the working practices of the officers struggling to prevent their occurrence. By deploying a qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
0
11
1
4
Order By: Relevance
“…Compared to prior research, our findings indicated that motivations for honor crimes involving children have a broader range of justifications and were also more likely to involve fathers as the perpetrators (Doğan 2014a;Kulwicki 2002). The individuality associated with adolescence is unique to westernized post-industrial nations.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Compared to prior research, our findings indicated that motivations for honor crimes involving children have a broader range of justifications and were also more likely to involve fathers as the perpetrators (Doğan 2014a;Kulwicki 2002). The individuality associated with adolescence is unique to westernized post-industrial nations.…”
Section: Discussioncontrasting
confidence: 64%
“…The findings from the current study indicated the motivation of the offense along with the relationship between the victim and offender must be considered since offenders murdered individuals in the name of honor outside their primary target. Overall, the characteristics of honor crimes in the United States maintain some similarities from documented international honor crimes (Doğan 2014a), but differences also emerged. It is hoped that future research continues to investigate this important area.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Weil'in (2016bWeil'in ( , s. 1126 belirttiği gibi, görünürlük sosyal bilimcilerin toplumsal olguları görüp görmediklerini, ya da nasıl gördüklerini, radikal bir biçimde şekillendirir. Kadınlara yönelen şiddetin ne ölçüde öldürücü boyutlara ulaştığını gözler önüne seren bu temsil biçimi, kadın cinayetlerini akademik bir görüş alanı içerisine taşımakta oldukça etkili olmuş gibi görünüyor: Son yıllarda, adli tıp (Ozgun Unal, Koc, Unal, Akcan, & Javan, 2016;Toprak & Ersoy, 2017), hukuk (Doğan, 2014), ruh sağlığı (Tosun Altınöz, Altınöz, Utku, Eşsizoğlu, & Candansayar, 2018) ve sosyoloji (Çetin, 2015;Taşdemir Afşar, 2016) gibi alanlardan çalışmalar Türkiye'de kadın cinayetlerinin farklı yönlerini mercek altına almaya başladı.…”
Section: Introductionunclassified